Endothelial TRPV4 channels mediate dilation of cerebral arteries: impairment and recovery in cerebrovascular pathologies related to Alzheimer's disease. (17th September 2013) - Zhang, Luqing; Papadopoulos, Panayiota; Hamel, Edith
Abstract : Background and Purpose: Transient receptor potential vanilloid type 4 (TRPV4) channels are expressed in brain endothelial cells, but their role in regulating cerebrovascular tone under physiological and pathological conditions is still largely unknown. Experimental Approach: Wild‐type (WT) mice and mice that overexpress a mutated form of the human amyloid precursor protein (APP mice, model of increased amyloid β), a constitutively active form of TGF‐β1 (TGF mice, model of cerebrovascular fibrosis) or both (APP/TGF mice) were used. Dilations to the selective TRPV4 channel opener GSK1016790A (GSK) or to ACh were measured in posterior cerebral artery segments. Key Results: Both GSK‐ and ACh‐induced dilations virtually disappeared following endothelium denudation in WT mice. These responses were impaired in vessels from APP, TGF and APP/TGF mice compared with WT. Pre‐incubation of WT vessels with the selective TRPV4 channel blocker HC‐067047, or with small‐conductance (SK channel, apamin) and/or intermediate‐conductance (IK channel, charybdotoxin, ChTx) Ca 2+ ‐sensitive K + channel blocker abolished GSK‐induced dilations and massively decreased those induced by ACh. These treatments had no or limited effects on ACh‐induced dilation in vessels from APP, TGF or APP/TGF mice, and IK and SK channel function was preserved in transgenic mice. Antioxidant superoxide dismutase or catalase normalized GSK‐ and ACh‐mediated dilations only in APP brain arteries. Conclusion and Implications: We conclude that endothelial TRPV4 channels mediate ACh‐induced dilation in cerebral arteries, that they are impaired in models of cerebrovascular pathology and that they are sensitive, albeit in the reversible manner, to amyloid β‐induced oxidative stress.